The Influence of Digital Promotion on Digital Repurchase Intention with Digital Brand Awareness as a Mediating Variable in the Fashion Industry on Social Media - Zulfan Baihaqi; Ardian Adhiatma (Cahaya Abadi Publisher, 2026)
This study aims to analyze the effect of digital promotion on digital repurchase intention, with digital brand awareness as a mediating variable in the fashion industry on social media. The background of this study is based on the increasing digital promotional activities carried out by fashion brands through various social media platforms such as Instagram, TikTok, and Facebook, which utilize interactive visual content to build brand awareness and encourage consumer repurchase intentions. This study uses a quantitative approach with an explanatory research method. Data were obtained through the distribution of online questionnaires to 150 Generation Z respondents aged 18-35 years who actively use social media and have purchased fashion products online. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of the SmartPLS program. The results of this study are expected to explain the extent of the influence of digital promotion on consumer repurchase intentions, as well as how digital brand awareness mediates this relationship. These findings are expected to provide theoretical contributions to the development of digital marketing literature, as well as practical benefits for fashion business actors in designing effective digital promotional strategies to build brand awareness and increase purchasing loyalty of Generation Z.